COMPARISON OF PHYSICOCHEMICAL AND FUNCTIONAL PROPERTIES OF FLOUR AND STARCH EXTRACT IN DIFFERENT METHODS FROM AFRICA LOCUST BEAN (PARKIA BIGLOBOSA) SEEDS - Sankhon, Abdoulaye; Amadou, Issoufou; Yao, Wei-Rong; Wang, Heya; Qian, He; Sangare, Moustapha (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: African locust bean tree is an important food tree for both human and livestock such as husks and pods. It plays a very vital role in the rural areas. The aim of this study was to evaluate some physicochemical, mineral characteristics and functional properties of flour and starch extract produced from Parkia biglobosa seeds, using different methods. Material and methods: Three different methods were used for starch extraction in other to get the Starch yield (%),composition analysis for; moisture, protein, fat, ash and fiber contents of flour and starch extracts from Parkia biglobosa were determined on dry basis (db), by AACC method, color and PH value measurements was carried out using color flex spectrocolorimeter, and the official method of AOAC respectively. Pasting properties was determined and X-ray powder starch diffraction was used to examine the crystalline property of flour and starch extract. Gelatinization characteristics and in vitro starch digestibility were also determined, test results were processed using one-way analysis of variance (ANOVA). Results: Flour showed higher (P < 0.05), moisture content, fat, carbohydrate, amylopectine, and protein content than starch, while amylose content of this starch was higher (P<0.05). Phosphorus, sodium, magnesium, and potassium minerals content were higher in flour than starch. Pasting properties, gelatinisation, color, pH values, water and oil absorption capacity content of the flour were found to be higher than that of starch. The pasting characteristics showed a decrease of viscosity, final viscosity, set back value, breakdown, and pasting temperature of flour when compared to that of starch. Conclusion: From our results, we speculate that flour from native Parkia biglobosa grown in Guinea under controlled environmental conditions could be considered as an ideal RS material, whereas the extract Parkia starch could be an ideal SDS material. Therefore, these may offer an interesting alternative for food developers, depending on their characteristics and functional properties.